Digital Library Services During the Covid-19 Crisis: Librarians' Perspective - Vlaić, Andrea; Cupar, Drahomira (Bobcatsss, 2023)
The purpose of this paper is to show how Croatian libraries responded to the crisis caused by the outburst of the COVID-19 pandemic in early March 2020. This research covers period when almost all public services were in complete lockdown, including libraries. Croatian Institute of Public Health (HZJZ) and Civil Protection Headquarters issued a measures to restrict social gatherings, ‘non-essential’ shops working-hours, services and organization of sports and cultural events for 30 days (19/03/2020-19/04/2020). The aim of this research is to gather personal experience of public librarians during the complete lockdown. Theoretical background of this paper is grounded in crisis management. Dealing with the crisis include development positive attitude towards the crisis and the situation, setting up business activities organizations in line with environmental expectations and seeking opportunities in a crisis (Funda & Majić, 2011). This research will focus on the role of the library in the local community and wider, since during this period all library services were transferred in an online environment. This research is divided into two parts. The first part will use Tisno Public library as a case study and will show how it transformed and transferred their existing, everyday services into digital platforms, and also how librarians have adapted their existing services and how successful they were in implementing virtual content into their standard programs. The second part uses semi-structured interview with 10 public librarians in order to gain knowledge about personal experiences on their activities and how they personally dealt with the crisis. This research will answer following research questions: 1. How did Tisno Public Library and their librarians respond to crisis? 2. What difficulties did public librarians in Croatia experience during the COVID-19 lockdown period and how did they overcome them? This health crisis has shown that libraries can exist between traditional and digital libraries, i.e. librarians are adaptable to any situation and so called ‘traditional’ and digital services can easily coexist. Both, services provided in physical library can be equally good and beneficial to the patrons as those provided in the virtual environment. Results of the first part showed that due to local activities, the Tisno Public Library was the first to provide assistance to citizens in overcoming difficulties with access to information during the crisis. The second part of the research gave insight knowledge on personal view of the libraries on the crisis. This crisis has also demonstrated that libraries have increasing potential to reach diverse public domain and ensure access to information. The global pandemic of COVID-19 has created rising need for digital libraries service by providing more quality and free service, but it will not change the primary role of library. In response to the crisis, the American Library Association (ALA) surveyed the community public libraries to understand the immediate effects of the crisis on their business, staff, programs and services (ALA, http). It is important to bear in mind Skip Prichard’s words (OCLC): "These are unprecedented times for all of us. Libraries around the world are moving into the new and an insecure environment. Their commitment to sharing information and serving the communities has never been shaken” (OCLC, http).